2011
DOI: 10.1108/14630011111214419
|View full text |Cite
|
Sign up to set email alerts
|

Commercial service charge management: benchmarking best practice

Abstract: Purpose -The paper benchmarks compliance for 2010-2011 with the RICS Code of Practice for Commercial Service Charges 2006. Design/methodology/approach -Whether the proxy adopted is measured by floorspace or number of commercial office buildings, the sample size conforms to Kreycie and Morgan's determination for representative sample size. Data are generated directly from the original documents provided to commercial leaseholders to ensure authenticity and remove the need for third party reporting of said data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…ft. of floor space and incurred £65,640,389 in total certified annual service charge expenditure during 2013. In terms of floor space, the office sample represents 1 per cent of the estimated total floor provided by multi-let commercial offices in the UK (for a detailed account of the difficulties associated with estimating the total stock of commercial UK multi-let offices see Eccles et al, 2011). The sample includes buildings owned and managed by 67 and 38 unique landlords and managing agents, respectively.…”
Section: Research Methodology 21 the Datamentioning
confidence: 99%
See 2 more Smart Citations
“…ft. of floor space and incurred £65,640,389 in total certified annual service charge expenditure during 2013. In terms of floor space, the office sample represents 1 per cent of the estimated total floor provided by multi-let commercial offices in the UK (for a detailed account of the difficulties associated with estimating the total stock of commercial UK multi-let offices see Eccles et al, 2011). The sample includes buildings owned and managed by 67 and 38 unique landlords and managing agents, respectively.…”
Section: Research Methodology 21 the Datamentioning
confidence: 99%
“…Previous research in the field of commercial service charges has utilized an array of different data collection approaches (Jones Lang Lasalle, 2012;RealService, 2013;Calvert, 2008;Eccles and Holt, 2012;Holt et al, 2011;. While all of these studies have their respective merits, the most unbiased findings arise from content analysis of the actual service charge documents issued to occupiers by managing parties (Calvert, 2008(Calvert, , 2005Holt et al, 2011;Eccles et al, 2011;and Holt and Eccles, 2015). This JCRE 17,3 present paper uses data hand collected from the actual service charge documents supplied to occupiers at multi-let office buildings and retail shopping centres to assess their specific level of compliance with the RICS Code of Practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature review UK commercial service charges have, in the last few years, been the subject of increased professional scrutiny after many years of being seen as problematic, yet unimportant (see, e.g., Calvert, 2008;Eccles and Holt, 2009;Eccles et al, 2011;Holt, 2015). There has also been international discussion on the issue as well (see, e.g., Halvitigala, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the UK, occupier satisfaction surveys (UK Occupier Satisfaction Index 2007-2012, 2012; Property Industry, Alliance and CoreNet Global 2010) find a high level of frustration among tenants with service charge administration, which affects their overall satisfaction with the lease. Research has shown that tenants are often provided with service charge information that is untimely, inaccurate, incomplete and inconsistent (Eccles and Holt, 2010; Eccles et al , 2011; Edward and Krendel, 2007; Morgan, 2010; Property Solutions, 2014). As a result, there is an “expectations gap” between the service charge information that is required by tenants and what many landlords provide (Holt et al , 2011b).…”
Section: Introductionmentioning
confidence: 99%